2018
DOI: 10.5194/acp-18-11991-2018
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the evolution of physical properties and mixing state of black carbon particles: from near a major highway to the broader urban plume in Los Angeles

Abstract: Abstract. Black carbon (BC) particles can have deleterious human health consequences and impact regional and global climate. Uncertainties remain in part due to incomplete knowledge on the evolution of physical properties and mixing state of black carbon from sources to the remote atmosphere. We aim to understand how “road-to-ambient” processing and longer timescale aging in an urban plume affect black carbon physical properties. Refractory black carbon (rBC) was measured during summer 2016 using a single-part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 58 publications
3
16
0
Order By: Relevance
“…Though a number of different proposed model treatments give different predictions of BC mixing state (Jacobson, 2001;Murphy et al, 2006;Péré et al, 2009), none of these give perfect agreement with atmospheric observations, either in situ or remote (Fierce et al, 2016). As the coated BC particles may act as cloud condensation nuclei (CCN) in the atmosphere, the coating thickness information of BCcontaining particles can also influence the wet removal rate and thus its atmospheric lifetime and overall climate forcing potential (Kuwata et al, 2007;Schroder et al, 2015;Motos et al, 2019). Taylor et al (2014) shows that the size distribution of BC-containing particles is important for the simulation of BC lifetime, vertical profile and transportation.…”
mentioning
confidence: 99%
“…Though a number of different proposed model treatments give different predictions of BC mixing state (Jacobson, 2001;Murphy et al, 2006;Péré et al, 2009), none of these give perfect agreement with atmospheric observations, either in situ or remote (Fierce et al, 2016). As the coated BC particles may act as cloud condensation nuclei (CCN) in the atmosphere, the coating thickness information of BCcontaining particles can also influence the wet removal rate and thus its atmospheric lifetime and overall climate forcing potential (Kuwata et al, 2007;Schroder et al, 2015;Motos et al, 2019). Taylor et al (2014) shows that the size distribution of BC-containing particles is important for the simulation of BC lifetime, vertical profile and transportation.…”
mentioning
confidence: 99%
“…In summer, the primary emissions are less compared to winter, and SOA contributes more in Beijing (Sun et al, 2018;Hu et al, 2016). Previous studies show that an internal mixture would be expected for BC associated with a larger secondary fraction (Krasowsky et al, 2018;Bondy et al, 2018). In addition, the rBC-containing particles experience more intense photochemical processing in summer, which may promote the formation of secondary species internally mixed with BC (Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…The campaign-wide f lag,neg was 0.017 for the first campaign (September 2017), 0.018 for the second campaign (December 2017), and 0.026 for the third campaign (November 2018). Comparatively, Dahlkötter et al (2014) observed an f lag,neg of ∼ 0.046 during an airborne field campaign measuring an aged biomass burning plume, and additionally calculated a higher fragmentation rate of ∼ 0.4 to 0.5, based on their aforementioned alternative method (Laborde et al, 2012). Sedlacek et al (2012) reported an f lag,neg > 0.6 for ground-based measurements of a biomass burning plume in Long Island, New York, originating from Lake Winnipeg, Canada.…”
Section: Negative Lag Times and Rbc Morphologymentioning
confidence: 98%
“…The incandescence signal was calibrated using Aquadag, and the scattering signal was calibrated using polystyrene latex spheres. Further details regarding the governing principles and operation of the SP2 can be found in numerous publications (Stephens et al, 2003;Schwarz et al, 2006;Gao et al, 2007;Moteki and Kondo, 2007;Laborde et al, 2012;Dahlkötter et al, 2014;Krasowsky et al, 2016).…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation